PPKN Sebagai Tonggak Rasa Patriotisme dan Nasionalisme Berkaitan dengan Identitas Nasional Bangsa Indonesia - Kaamilah Nurnazhiifa; Dinie Anggraeni Dewi (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Citizenship education is an integral part of the education system. Therefore, the civic education process needs to be carried out by courses and learning at all streams and levels of education. Functions and roles to achieve the goals of national education, civic education, develop, implement and apply in the context of the realization of the goals of national education. These three things become the basis and framework for thinking about and implementing Citizenship Education. There are several reasons why civic education is needed, namely symptoms and trends in non-political literacy or "political literacy" and not knowing how democracy and its system work; second, increasing political apathy is indicated by the participation of the most intellectual, emotional citizens. This is where the existence of Citizenship education is a very important tool for a democratic country, including Indonesia, to give birth to a country that is passed down from generation to generation and understands the values of the nation which is based on Pancasila and has skills.